Impact of IPDC Finance Limited on small business entrepreneurs through Sheba. XYZ project - Rashid, Faheem Nur (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.